Trends in immune-related adverse events for colorectal cancer: A bibliometric analysis - Cui, Jin; Xiong, Ying; Sun, Min; Gu, Xinyue; Liu, Yuting; Zhong, Luhui; Hong, Xiaohua; Liu, Li (Frontiers in Oncology, 2022)
Purpose We used bibliometric methods to assess the global scientific output on the IRAEs for colorectal cancer and to explore the current status and trends in the field over the last three decades. Methods Studies on immune-related adverse events for colorectal cancer published from 1996 to 2022 were retrieved from the Web of Science. For quantitative and qualitative assessments of publication outputs and author contributions, the R bibliometrix package was used. VOSviewer was used to construct networks based on the co-authorship of countries/institutions/authors, co-citation analysis of journals/references, citation analysis of documents, and co-occurrence of keywords. Results A total of 237 relevant articles were included in the final analysis. The number of publications has increased significantly over time. The countries and institutions that contributed most to the field were the USA and the University of Texas MD Anderson Cancer Center. Jefferey Schlom was the most productive author, ranking first in cited authors. The most cited document was Topalian et al. in The New England Journal of Medicine (2012). The journals with the highest number of selected articles and citations were The New England Journal of Medicine and the Journal of Clinical Oncology, respectively. Co-occurrence analysis showed that IRAEs for colorectal cancer were associated with immunotherapy, open-label, chemotherapy, nivolumab, and PD-1. Trend analysis showed that immune checkpoint inhibitors, gut-microbiota, inflammatory-bowel disease, and PD-1has been on the rise in recent years to IRAEs for colorectal cancer. Conclusion Our bibliometric analysis showed that studying IRAEs for colorectal cancer is increasingly a hot topic. The focus of the research had evolved from traditional treatment modalities such as targeted therapy to gut microbiota. Inflammatory bowel disease may be a future research hotspot of IRAEs for colorectal cancer.